2006
DOI: 10.2172/882552
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions Involving Dissociated States of Water at the Electrochemical Ni(111)/H2O Interface

Abstract: 2 Electrochemical processes occurring in aqueous solutions are critically dependent upon the interaction between the metal electrode and the solvent. In this work we use density functional theory to calculate the range of potentials for which molecular water and its activation products (adsorbed hydrogen and hydroxide) are stable when in contact with an immersed Ni(111) electrode. Changes in the adsorption geometries of water and its dissociation products are also determined as functions of potential. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This size of the surface may not be large enough to fully capture the influence of coadsorbed water which can act to stabilize the intermediates and products. The approach taken by Filhol was later extended by Taylor et al [44] over Cu(111), and used to examine a broader range of potentials. A number of these issues were removed by ultimately using a much larger 3 9 3 unit cell as well as external reservoirs to solvate the H + /OH -species that form.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This size of the surface may not be large enough to fully capture the influence of coadsorbed water which can act to stabilize the intermediates and products. The approach taken by Filhol was later extended by Taylor et al [44] over Cu(111), and used to examine a broader range of potentials. A number of these issues were removed by ultimately using a much larger 3 9 3 unit cell as well as external reservoirs to solvate the H + /OH -species that form.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study showed that, as the potential was increased from the potential of zero charge, water was activated to form surface hydroxide intermediates followed by a surface oxide layer that formed at further increases of the potential. At high enough potentials, the adsorbed oxygen and the surface Cu atoms exchange places ultimately leading to the dissolution of solvated Cu 2+ ions and a passivating Cu 2 O overlayer atop the Cu(111) surface [44].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, many studies are progressively revealing the atomic-level details of the electrode reactions at water electrolysis cells. [122][123][124][125] Early electrolysis cells were about 60-75% efficient. However, the current small-scale, best-practice figure is close to 80-85%, with larger units being a little less efficient (ca.…”
Section: Future Trendsmentioning
confidence: 99%
“…In this work, we present a kinetic study of the HOR/HER on Ni electrodes in the pH range from 12 to 14. Since the HOR/HER activity of Ni is rather low due to the strong hydrogen binding to the surface, it is usually enhanced either by partially oxidizing Ni surfaces or by combining Ni with other non‐noble transition metals such as Mo, Cr, Co or Cu . Hence, to have a better understanding of the pH dependence, along with metallic Ni, in this work we also explore a partially oxidized Ni as well as a NiCu/C electrode.…”
Section: Introductionmentioning
confidence: 99%